Molecular Identification and Prevalence of Tick (Rhipicephalus sanguineus) Infestation in Dogs from Guwahati, Assam, India - Bhowmik, Pratik; Neog, Ranjeet; Bhattacherjee, Kanta; De, Ankan; Saikia, Deep Prakash (International Journal of Bio-resource and Stress Management, 2024)
The experiment was conducted in and around Guwahati, Assam, India for a period of one calendar year from March, 2021 to February, 2022 to determine the prevalence and molecular identification of tick infestation in dogs in and around Guwahati, Assam, India. A total of 582 dogs of different breeds, age groups (below 1 year and above 1 year age group), sex and different categories (stray dogs, pet dogs and working dogs) were examined. Study revealed that overall prevalence of tick was found to be 58.76%. Breed-wise, highest prevalence of tick infestation was observed in mongrels (75%) followed by Germam shepherd (66.66%). Sex-wise, tick infestation was more in male dogs (70.10%) than females (47.42%). According to the age, tick infestation was found more in dogs of below 1 year of age (89.38%) than in dogs of above 1 year of age (39.32%). Category wise, stray dogs (92.77%) showed higher prevalence of tick infestation than working (64.36%) and pet dogs (40.12%). Ticks were observed throughout the year of which highest prevalence was recorded in monsoon season (70.79%) followed by post monsoon (62.22%), pre monsoon (57.35%) and winter (36.92%). Morphological as well as molecular identification based on amplification and sequence analysis of the 16S rRNA gene showed that the isolated ticks belonged to Rhipicephalus sanguineus (ON428306.1, ON428307.1 and ON428308.1). Phylogenetic analysis based on a portion of 16S rRNA gene showed divergence at nucleotide level among the tick isolates.